The signalling roles of sphingosine‐1‐phosphate derived from red blood cells and platelets - Tukijan, Farhana (Br J Pharmacol, 2018)
Sphingosine‐1‐phosphate (S1P) is an essential, bioactive lysophospholipid mediator that regulates various physiological functions such as lymphocyte trafficking, inflammation and behavioural characteristics of the vascular system. S1P signalling is mediated via a family of five GPCRs, which are expressed in various cell types and tissues. S1P concentration is maintained in a gradient through the activity of S1P degrading enzymes, and this gradient is critical for lymphocyte egress. To exert its extracellular signalling roles, S1P must be secreted out of the cells by protein transporters. The recent discovery of S1P transporters has shed light on the sources of S1P. However, these transporters still need to be clarified as they are important in defining the S1P gradient for lymphocyte recirculation and the source of S1P for maintenance of blood vessels. Here, we review the current understanding of S1P sources, highlighting the roles of S1P transporters with an emphasis on haematopoietic cells as a major source of circulatory S1P.